Telemedicine for Indian primary health centres: is there a need for super specialist consultation. (2016) - Maheshwari, Sunita; Kalyanpur, Arjun; Mehra, Chhavi; Seshadri, Srikrishna; Thomas, Sheeba
Although Indian healthcare is booming it faces huge challenges in the area of rural healthcare delivery. Both public and private healthcare providers have been trying different models to reach out to the rural areas for providing primary healthcare and one of the major initiatives in this direction has been telehealth. Though there were few successful models, telehealth initiatives in general faced many challenges from inadequate infrastructure, unskilled paramedics and a lack of sustainable economic and business model. This paper analyses a private healthcare providers experience in conducting 16, 609 teleconsultations across rural India using Cisco's health presence and focuses on identifying specialists need in the rural area and methods to address those needs in an India specific context.